Driving performance and road sign identification by multifocal contact lens wearers in a driving simulator. Issue 4 (August 2022) - Fogt, Jennifer Swingle; Kerwin, Thomas; Wrabel, Cameron; Schomer, Casey; Fogt, Nick
Abstract: Purpose: The purpose of this study was to compare sign identification distances and driving performance metrics in presbyopic participants while wearing multifocal contact lenses (MFCL) and while wearing progressive addition lens (PAL) spectacles. Methods: 19 presbyopic participants completed PAL spectacle assessments and contact lens fitting and follow up visits before driving assessments began. These assessments occurred in a simulator equipped with a full-sized sedan on a motion platform and a 260 degree screen. Participants completed the driving task with PAL and with MFCL. Participants followed a lead car and identified signs at various distances from the road. For the two wearing conditions, comparisons of the distance along the road at which signs were identified were made using repeated measures ANOVA. Paired t-tests were used to compare driving performance for the two conditions. Results: There was no statistical difference in sign identification distance between PAL and MFLC for signs 32.0 m from the road side of the road (182 ± 46 m for MFCL; 205 ± 45 m for PAL; P = 0.07) or 51.4 m from the side of the road (204 ± 43 m for MFCL; 216 ± 36 m for PAL; P = 0.3). Only signs 70.2 m from the roadside showed a significant difference (207 ± 42 m with MFCL; 232 ± 39 m with PAL; P = 0.01), All distances were greater than those required to safely stop a vehicle. There were no significant differences in the driving performance metrics between the refractive corrections. Conclusion: Driving performance metrics were similar for MFCL and PAL spectacles. Sign identification distances with both eyewear types were well within the distances required for safe vehicle stopping.